IMPROVEMENTS TO THE STATEMENT OF COMPREHENSIVE INCOME - Nodira Khasanova (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2026)
The statement of comprehensive income has become one of the most important components of modern financial reporting, reflecting not only an entity’s operating performance but also unrealized gains and losses arising from changes in market conditions. In Uzbekistan, ongoing economic reforms, gradual adoption of International Financial Reporting Standards (IFRS), and increasing integration into global capital markets necessitate substantial improvements in the structure, transparency, and analytical value of the statement of comprehensive income. This study aims to examine the current practice of comprehensive income reporting in Uzbekistan, identify existing methodological and institutional limitations, and propose directions for improvement aligned with international standards and national economic priorities. The research employs comparative analysis, statistical trend evaluation, and synthesis of international best practices. The findings indicate that clearer classification of other comprehensive income (OCI), enhanced disclosure requirements, and harmonization with IFRS can significantly improve the reliability and usefulness of financial information for investors, regulators, and other stakeholders. The paper contributes to the literature by providing policy-oriented recommendations tailored to the Uzbek accounting environment.